Research on the Scattering Characteristics and the RCS Reduction of Circularly Polarized Microstrip Antenna. (14th July 2013) - Jiang, W.; Hong, T.; Gong, S. X.
Abstract : Based on the study of the radiation and scattering of the circularly polarized (CP) antenna, a novel radar cross-section (RCS) reduction technique is proposed for CP antenna in this paper. Quasi-fractal slots are applied in the design of the antenna ground plane to reduce the RCS of the CP antenna. Both prototype antenna and array are designed, and their time-, frequency-, and space-domain characteristics are studied to authenticate the proposed technique. The simulated and measured results show that the RCS of the prototype antenna and array is reduced up to 7.85 dB and 6.95 dB in the band of 1 GHz–10 GHz. The proposed technique serves a candidate in the design of low RCS CP antennas and arrays.